Additively manufactured heterogeneous substrates for three‐dimensional control of local permittivity. Issue 10 (1st May 2014) - Tribe, J.; Whittow, W.G.; Kay, R.W.; Vardaxoglou, J.C.
Abstract : The concept of using additive manufacturing as a method to construct heterogeneous substrates from a single building material via stereolithography is introduced. The dynamic variation of air cavities within the bulk material is used to control the effective permittivity of the host medium. The digitally driven layer process enables full three‐dimensional variation of the local permittivity. The high resolution of stereolithography enables sub‐millimetre control of air inclusion features. Measurements of the effective permittivity with different air fractions have been compared to analytical results.